THE EFFECTIVENESS OF GUAVA LEAVES IN THE LONG TIME HEALING OF PERINEAL WOUNDS OF POSTPARTUM MOTHERS AT MIDWIFES INDEPENDENT PRACTICE IN BENGKULU CITY - Sri Yanniarti; Rosmala Aprelia; Epti Yorita; Rialike Burhan (Proceeding B-ICON, 2023)
Based on data from the World Health Organization, the direct causes of death in other countries are the same, namely bleeding (28%), eclampsia (24%) and postpartum infection (1%). There are infections with a proportion (20-30%) of cases of infection caused by infection of the birth canal or perineal rupture. Cases of laceration or rupture of the perineum in maternity women worldwide occur in 2.7 million people. Based on the results of a survey conducted at one of the Independent Practices of Midwives in Bengkulu City, data on the number of mothers giving birth from January-July 2021 was 58 people and the incidence of perineal injuries with episiotomy was 38 mothers (65%). The average perineal wound healing time is 7-10 days. The design used in this study was a quasi-experimental. The sampling technique in this study was accidental sampling. The total number of samples was 15 respondents in the guava leaf group and 15 respondents in the comparison group. Statistical analysis used is the Mann Whitney test. The results of this study were the average length of perineal wound healing with guava leaves was 5.47 days, while for binahong leaves it was 5.63 days. There is an effect of guava leaves on the duration of perineal wound healing with a p value of 0.003 which means that guava leaves are effective on the duration of perineal wound healing in postpartum mothers. The most dominant influence of other variables on perineal wound healing is nutritional intake.